Ease of Navigation of Uniqlo.com as a Key Consumer Behavior in Purchasing Clothing Online - Dewi, Erika Kusuma; Cahyaningrum , Yuniana (Expert Net: Exploration Journal of Technological Education Trends, 2024)
This research addresses ease of navigation on the Uniqlo.com website as a key factor in consumer behavior when making online clothing purchases. With the increasing use of the internet in Indonesia, Uniqlo seeks to utilize digital platforms to attract customers. The research method used is qualitative with a descriptive approach, which includes analyzing the interface design, search features, and payment process on the website. The results show that intuitive design and clear product categories improve the user experience, thus driving consumer satisfaction and loyalty. This research provides insight into the importance of website optimization in online marketing strategies.